Mathematics Subject Matter In Two Different Curriculum Perspective - Kurniati, Lenny; Kusumawati, Ratih (Urogram Studi Pendidikan Matematika, Universitas Ivet, 2024)
Curriculum transformation is essential to the education because it aims to improve learning quality and make it more relevant to the needs of students and society. The curriculum can be adapted to align the course content with current issues and the society's demands. Modifying or updating materials enables the curriculum to address current issues better and provide knowledge that aligns with the needs of the students. The purpose of this study is to analyze the differences in mathematics teaching materials for junior high school students based on the transformation of the 2013 curriculum to the ‘Merdeka’ curriculum. The research methodology employed in this study is a literature review, with the primary sources that are the government regulations outlining the fundamental competencies of the 2013 curriculum and the learning outcomes of the Merdeka curriculum, as well as other supporting relevant references. According to the findings, the Merdeka curriculum has less material than the 2013 curriculum. This aligns with Merdeka curriculum's characteristics, which prioritize essential material to provide ample time for students to develop their creativity and innovation skills.